Differential sensitivity of mucosal organs to transient exposure to hydrogen sulphide in post-smolt Atlantic salmon (Salmo salar) - Alipio, Hanna Ross D.; Hansen-Bergstedt, Julie; Lazado, Carlo C. (Aquaculture, 2023)
Mortality related to hydrogen sulphide (H2S) has recently become a serious concern in Atlantic salmon (Salmo salar) farming, particularly in saline recirculating aquaculture systems (RASs), where the risk of H2S formation is high. H2S has a distinct odour of rotten eggs, and its production is associated with the anaerobic bacterial decomposition of protein and other sulphur-containing organic matter. Significant advances have been made in elucidating its formation in RAS, but the biological consequences of this toxicant in salmon remain elusive. We report the physiological consequences of transient exposure of post-smolt Atlantic salmon to H2S. The fish were exposed to one of three levels of H2S for 1 h: 0 µM (unexposed), 0.6 µM (low exposure), and 1.2 µM (high exposure). Fish were allowed to recover for 24 h and then sampled for gene expression, histology, and metabolomics analyses. Molecular profiling was performed on a subset of genes with known functions in sulphide detoxification, mucins, immunity, and stress responses, which focused on the gills, olfactory organ, skin, and distal gut. With the exception of interleukin 10, all genes studied were significantly affected in the skin, where high H2S triggered significant upregulation. Stress-related genes were mostly affected in the gills, where the high H2S level also induced significant upregulation. Downregulation of the marker genes was identified in the olfactory organ especially in the low-dose group. The distal gut was less sensitive to H2S, regardless of the dose. Histological health scoring of the four mucosal organs revealed no substantial structural alterations and only sporadic cases of mild-moderate unspecific tissue damage. High-throughput metabolomics revealed that transient H2S exposure had a substantial mucosal impact rather than a systemic impact, as shown by changes in skin mucus metabolome. Functional annotation indicated that 10 metabolomic pathways were significantly affected in the skin mucus, including tRNA charging, the superpathway of ...